International Trade Unionism in a Globalizing World : A Case Study of New Labour Internationalism - Ghigliani, Pablo (Economic and Industrial Democracy.)
In recent years, scholars and activists have identified the development of an emerging new labour internationalism (NLI), and pointed to its impact upon the structures and practices of international trade unionism (ITU). This article addresses this issue through a case study of an international action opposing the labour practices of McDonald?s, the world?s largest fast-food retailer. The evidence reveals a complex picture. Even though many of the features of the allegedly new labour internationalism are present, they seem to be more a matter of form than substance.